Financial Integration Through Equity Markets and the Role of Exchange Rate: Evidence from ASEAN-5 Countries - Hawati Janor; Ruhani Ali; Roselee Shah Shaharuddin (Asian Academy of Management Journal of Accounting and Finance, 2007)
This study explores equity market integration for five major ASEAN countries: Malaysia, Singapore, Thailand, Philippines and Indonesia. The motivation emanated from the fact that these countries have been implementing financial reforms in their attempt to promote economic efficiency. By applying the bivariate and multivariate cointegration techniques we test whether ASEAN-5 stock markets are globally or regionally integrated. For the global markets, the study focus on the role of the US, Japan and world market. The importance of exchange rate on the integration is examined under the multivariate framework. The study also address the possible impact of 1997 Asian financial crisis on the integration. While the findings revealed that some of these markets are regionally and globally integrated, the integration however is not fully complete, thus reflect some diversification benefits in these markets. The study also support previous findings that documented evidence on the increasing influence of Japan on ASEAN countries relative to the US. The study also shows significant impact of the financial crisis and provide evidence on the importance of exchange rate on the integration.